The mediating role of consumer-company identification on the link between corporate social responsibility and consumer loyalty: a South African perspective - Mothibeli, Hopolang (My University, 2022)
As Corporate Social Responsibility (CSR) increases in relevance and more firms engage in these activities with the aim to build consumer loyalty, this research report used the Relational Competence Theory to investigate the effect of CSR on the development of social bonds between businesses and consumers via Consumer-Company (C-C) identification to cultivate consumer loyalty intentions. The aim of the study was to contribute to a knowledge gap regarding the causal processes linking CSR to consumer loyalty as an outcome, with emphasis on the mediating role of C-C identification. The research objectives of the study were to determine the influence of CSR on consumer loyalty, the effect of CSR on C-C identification and the mediating role of C-C identification on CSR and customer loyalty relationship. The concepts central to the conceptual framework that was developed for the study through reviewing existing literature include CSR, CSR credibility, C-C Identification, trust, and consumer loyalty. These concepts informed the data collection tool employed in a correlational and cross-sectional research study to collect quantitative data from 233 respondents in a selfadministered online questionnaire consisting of close-ended questions. The population parameters for the study sample included South African adults aged eighteen and above living in Johannesburg and the convenient sampling method was employed to recruit participants that were conveniently available given time and resource limitations. The data was analysed using EFA, CFA and SEM in R software to provide findings used to address the research problem and research questions. CSR was found to have a non-significant impact on loyalty while CSR credibility was found to positively influence CC-Identification which influences loyalty. Trust was found to be the cornerstone to building loyalty.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Corporate social responsibility (CSR); CSR credibility; Consumer loyalty; SDG-8: Decent work and economic growth